Institutional and Policy Analysis of River Basin Management : The Warta River Basin, Poland - Blomquist, William (World Bank, Washington, DC, 2012)
The authors describe and analyze the emergence of river basin management in the Warta River Basin of Poland. The Warta basin's 55,193 k